Altered bowel habit and rectal bleeding in pregnancy: the importance of recognising undiagnosed inflammatory bowel disease. Issue 3 (18th March 2021) - Singh, Gurpreet; Prentice, Ralley; Langsford, David; Christensen, Britt; Garg, Mayur
Abstract: Worsening of disease activity during pregnancy in patients with known inflammatory bowel disease, especially ulcerative colitis (UC), is well recognised, but the diagnosis of new‐onset or previously undiagnosed UC in pregnancy has been inadequately studied to date. Recognition of gastrointestinal symptoms in pregnancy as potentially indicating UC is of paramount importance, as this allows appropriate investigation and instigation of therapies to optimise maternal and foetal outcomes. Here, we report three cases of women with gastrointestinal symptoms in pregnancy with disparate outcomes.